2009
DOI: 10.1161/strokeaha.108.529537
|View full text |Cite
|
Sign up to set email alerts
|

LDL Cholesterol and the Development of Stroke Subtypes and Coronary Heart Disease in a General Japanese Population

Abstract: Background and Purpose-Although the relation between serum LDL cholesterol level and coronary heart disease (CHD) is well established, its relation with stroke subtypes is less clear. Methods-A total of 2351 inhabitants age Ն40 years in a Japanese community were followed up for 19 years. Results-During follow-up, 271 subjects developed stroke and 144 developed CHD. Whereas the age-and sex-adjusted incidences of CHD significantly increased with increasing LDL cholesterol levels (P for trend Ͻ0.001), the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(148 citation statements)
references
References 44 publications
6
125
1
3
Order By: Relevance
“…Covariates included in Cox's proportional hazards model were age, sex, systolic blood pressure, diabetes, LDL cholesterol, highdensity lipoprotein cholesterol and smoking habits that were traditional risk factors for cardiovascular disease established in the Hisayama study. 16,17,20,21 The performance of the risk prediction model was then tested among subjects allocated to the validation cohort. Ability of the risk prediction model to discriminate persons who experience a cardiovascular disease from those who do not were evaluated using c-statistic, 24 and calibration of the risk prediction model was evaluated using a Hosmer-Lemeshow w 2 -statistic with 8 d.f.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Covariates included in Cox's proportional hazards model were age, sex, systolic blood pressure, diabetes, LDL cholesterol, highdensity lipoprotein cholesterol and smoking habits that were traditional risk factors for cardiovascular disease established in the Hisayama study. 16,17,20,21 The performance of the risk prediction model was then tested among subjects allocated to the validation cohort. Ability of the risk prediction model to discriminate persons who experience a cardiovascular disease from those who do not were evaluated using c-statistic, 24 and calibration of the risk prediction model was evaluated using a Hosmer-Lemeshow w 2 -statistic with 8 d.f.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that LDL cholesterol, as a continuous variable, did not reach statistical significance in the derivation cohort. However, LDL cholesterol is an established risk factor for cardiovascular disease in the Hisayama study 21 and thus we included LDL cholesterol into the risk prediction model. A third limitation is that our findings are based on a one-time measurement of risk factors (for example, systolic blood pressure, plasma glucose levels, LDL cholesterol levels and high-density lipoprotein cholesterol levels), which may not accurately reflect the status of a study participant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many Japanese cohort studies, including the Hisayama study, have clearly shown, a high level of serum LDL cholesterol is a risk factor for CHD, but not for stroke. 12,13 Third, their risk score sheet is based on a cohort study in one rural town. Accordingly, this score sheet may be limited in its generalizability to urban populations, in which the incidence of CHD is much higher than in rural populations.…”
mentioning
confidence: 99%